The Yin–Yang Definition Model of Mental Health: The Mental Health Definition in Chinese Culture - Wang, Kai (Frontiers in Psychology, 2022)
It is a common aim of psychologists to construct a definition model with universal cultural applicability for mental health. These models can be divided into two types in terms of definition: One is the negative mental health definition model based on the absence of mental illness symptoms; the other is the definition model of positive mental health based on subjective feelings, such as happiness and social identity. However, neither of these definitions can properly explain Chinese people’s understanding of mental health or how mental health is dealt with in Chinese culture. This paper proposes a Yin–Yang definition model of mental health based on the theory of personality of Confucianism and Taoism. This model not only properly describes the understanding of mental health in traditional Chinese culture, but also explains East Asian psychotherapy and mental health practices in the context of Chinese culture.